Evaluation of Heavy Metals Content in Fresh and Canned Sardines Produced in Some Mediterranean Countries. (Libyan Journal of Ecological & Environmental Sciences and Technology, 2023)
Most heavy metals which bio-accumulate in fishes do not have any biological significance or beneficial use, but due to the presence of heavy metal, fish can pose a health risk to consumers. The present investigation was carried out to evaluate the Concentrations level of mercury (Hg), cadmium (Cd), and lead (Pb) in Sardines available in the Libyan market and produced in different countries of the Mediterranean region. All collected samples were analyzed by graphite furnace atomic absorption spectrometry after microwave assisted digestion, for detection of their contents of heavy metal residues to evaluate their quality according to standard legislations. The obtained results indicated concentrations for lead and mercury ranges from (0.0070 -  0.0125) and (0.0 - 0.0095) mg/kg respectively. It was observed that the levels of Lead and Hg in all different samples were within the permissible limits according to the standards of the World Health Organization and the European Union.
Keywords: heavy metals; Sardines; Libyan market; Mediterranean region; atomic absorption spectrometry